JURIDICAL ANALYSIS OF THE APPLICATION OF RESTORATIVE JUSTICE IN CASE OF NARCOTICS ABUSE IN THE DIRECTORATE OF DRUGS, POLDA KEPRI - Sitanggang, Darsono; Parroha Patar Siadari, Lagat; Dahlan, Dahlan (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
The construction of the journal topic above is: "Juridical Analysis of the Application of Restorative Justice in Narcotics Abuse Cases at the Directorate of Narcotics of the Riau Islands Police", with the formulation of the problem: What is the Legal Arrangement, Implementation and Supervision of the Application of Restorative Justice in Narcotics Abuse Cases at the Directorate of Narcotics of the Riau Islands Police? The type of writing is normative legal, using legal research methodology, supported by secondary data, and using a qualitative approach, and to obtain secondary data obtained through library research (library research), and to obtain primary data obtained through field research at the Directorate of Narcotics of the Riau Islands Police. For grand theory using the legal theory of policy by James E. Anderson, middle theory uses implementation law theory by Van Meter and Va Horn and applied theory uses Robert J. Mockler's supervisory law theory. The results of the analysis concluded that the legal arrangements for applying the concept of restorative justice to narcotics abusers committed by the Indonesian National Police have been regulated in Indonesian National Police Regulation Number 8 of 2021 concerning Handling of Crimes Based on Restorative Justice and SEMA Number 4 of 2010 concerning Placement of Victim Abuse Narcotics Abuse and Addicts into Medical and Social Rehabilitation Institutions. The application of restorative justice is very good for enforcing the law of narcotics abusers with the aim of returning to the original condition of the health of narcotics abusers.